2020
DOI: 10.3390/catal10121399
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Mn-Fe Catalysts Supported on Coal Fly Ash for Low-Temperature Selective Catalytic Reduction of NOX in Flue Gas

Abstract: A series of Mn0.15Fe0.05/fly-ash catalysts have been synthesized by the co-precipitation method using coal fly ash (FA) as the catalyst carrier. The catalyst showed high catalytic activity for low-temperature selective catalytic reduction (LTSCR) of NO with NH3. The catalytic reaction experiments were carried out using a lab-scale fixed-bed reactor. De-NOx experimental results showed the use of optimum weight ratio of Mn/FA and Fe/FA, resulted in high NH3-SCR (selective catalytic reduction) activity with a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 57 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…To investigate the adsorption state and species changes of NH 3 on the surface of AB-CFA-9, in situ DRIFTS was utilized to analyze its adsorption behavior and identify acid sites on the surface through the adsorbed species of NH 3 . , As shown in Figure b, the peaks observed at 1650–1690 and 1436–1380 cm –1 are attributed to the asymmetric bending vibration and symmetric bending vibration of the N–H bond in *NH 4 + species formed on Brønsted acid sites, which explains the appearance of a broad band at 503 °C on the NH 3 -TPD. ,, Similarly, peaks at 1605–1592 and 1282–1120 cm –1 are attributed to the symmetric bending vibration and asymmetric bending vibration of the N–H bond in *NH 3 adsorbed on Lewis acid sites, which corresponds to the sharp band at 586 °C on NH 3 -TPD. The peak at 1547 cm –1 is attributed to −NH 2 species. , Additionally, vibrational peaks at 1060–960 cm –1 are attributed to the adsorbed unstable gaseous NH 3 on the sample surface …”
Section: Resultsmentioning
confidence: 99%
“…To investigate the adsorption state and species changes of NH 3 on the surface of AB-CFA-9, in situ DRIFTS was utilized to analyze its adsorption behavior and identify acid sites on the surface through the adsorbed species of NH 3 . , As shown in Figure b, the peaks observed at 1650–1690 and 1436–1380 cm –1 are attributed to the asymmetric bending vibration and symmetric bending vibration of the N–H bond in *NH 4 + species formed on Brønsted acid sites, which explains the appearance of a broad band at 503 °C on the NH 3 -TPD. ,, Similarly, peaks at 1605–1592 and 1282–1120 cm –1 are attributed to the symmetric bending vibration and asymmetric bending vibration of the N–H bond in *NH 3 adsorbed on Lewis acid sites, which corresponds to the sharp band at 586 °C on NH 3 -TPD. The peak at 1547 cm –1 is attributed to −NH 2 species. , Additionally, vibrational peaks at 1060–960 cm –1 are attributed to the adsorbed unstable gaseous NH 3 on the sample surface …”
Section: Resultsmentioning
confidence: 99%
“…Various characterization methods were used to understand the role of the physicochemical structure of the synthesized catalysts on their De-NOx capability, like scanning electron microscopy, physical adsorption-desorption, and X-ray photoelectron spectroscopy. Furthermore, NH 3 /NO temperature-programmed desorption, NH 3 /NO-thermogravimetric-mass spectrometry, and in situ DRIFTs (Diffuse Reflectance Infrared Fourier Transform Spectroscopy) results showed that the Mn 0.15 Fe 0.05 /FA has relatively high adsorption capacity and activation capability of reactants at low temperatures [ 75 ].…”
Section: Applications To Catalystmentioning
confidence: 99%
“…Cai et al [11] also demonstrated that the co-combustions of textile dyeing sludge and waste tea reduced SO 2 emission through thermogravimetric coupled with mass spectrometry (TG-MS) analysis. It is essential to quantify the release of gaseous pollutants in the co-combustion process of sewage sludge and gasification fine slag residual carbon, which can provide important inspiration for the control of pollutants in industrial burner in the future [25][26][27].…”
Section: Introductionmentioning
confidence: 99%